1999
DOI: 10.1177/088307389901400302
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic and Adaptive Functioning in Adolescents and Young Adults Shunted for Congenital Hydrocephalus

Abstract: The major aim of this study was to assess whether the syndrome of nonverbal learning disabilities described in hydrocephalic children is observed in adulthood. Eleven adults shunted for congenital hydrocephalus related to spina bifida and eight adults shunted for hydrocephalus related to aqueductal stenosis were administered an extensive neuropsychologic battery to investigate discrepancies between verbal and visuospatial cognition, verbal and visuospatial long-term memory, and psycho-social adaptive abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
6
29
0
Order By: Relevance
“…Eventually, the patients with hydrocephalus had significant impairment on the neurocognitive functions of their frontal, parietal and temporal lobes. On the other hand, the statistical analyses performed on demographic data showed that the aetiology of the hydrocephalus, age, sex and localization of the shunt (frontal or posterior parietal) did not affect the test results, as reported in the literature 12) ; it could therefore be said that these difficulties may be caused by hydrocephalus itself and not the aetiological factors.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Eventually, the patients with hydrocephalus had significant impairment on the neurocognitive functions of their frontal, parietal and temporal lobes. On the other hand, the statistical analyses performed on demographic data showed that the aetiology of the hydrocephalus, age, sex and localization of the shunt (frontal or posterior parietal) did not affect the test results, as reported in the literature 12) ; it could therefore be said that these difficulties may be caused by hydrocephalus itself and not the aetiological factors.…”
Section: Discussionsupporting
confidence: 50%
“…In literature, some authors suggested that although the hydrocephalus is apparently arrested, the disorder may progress and produce neuropsychological disturbances in certain patients. Recent study results have support this thesis that these patients have persistent neuropsychological difficulties affecting visuospatial, language skills and motor functions; and difficulties in other nonverbal domains such as attention, memory, maths, numeracy, and problem solving 3,12,14,22) . Because these problems with memory and concentration reduce intellectual ability and decrease performance in school, these patients have serious adaptive problems in their social, cultural, behavioral and academic life 11,12,14) .…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Additionally, previous studies have typically not included an ethnically diverse participant sample and/or have not reported the ethnicity of their participants (e.g., Barf et al, 2003;Dennis et al, 1981;Hommet et al, 1999;Iddon et al, 2004;Lindquist et al, 2009;Jenkinson et al, 2011;Snow, 1999;Snow et al, 1994). Due to this practice, the phenotype that is described in the literature may not be representative of children with lower intelligence or children of diverse ethnicities.…”
Section: Introductionmentioning
confidence: 99%